Implementasi Metode Talaqqi Dalam Meningkatkan Kualitas Bacaan Al-Qur’an Di Sma Islam Al-Ulum Terpadu Medan - Nur Aini; Nanda Rahayu Agustia; Abdi Syahrial Harahap (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aims to determine and analyze the implementation of the Talaqqi method in improving the quality of Al-Qur'an reading at Al-Ulum Terpadu Medan Islamic High School. The research method is qualitative with data collection techniques in the form of observation, interviews, and documentation. Data analysis with data reduction, data presentation, and drawing conclusions. The results of this study the researcher found (1). Implementation: The talaqqi method was implemented in the prayer room for grade X and XI students who had difficulty with letter pronunciation and tajweed. (2). Supervision and Evaluation: Conducted daily, weekly, and monthly through recording errors, peer listening methods, and routine coordination between teachers, homeroom teachers, and the school. (3). Supporting Factors: Good cooperation between tutors and homeroom teachers. (4). Inhibiting Factors: Limited time of 45 minutes, an unbalanced teacher-student ratio of 1:20, students' physical condition, and high academic load. (5). Results and Achievements: Improving the accuracy of Al-Qur'an reading. Understanding of tajweed and its application in reading.